International Competitiveness Indicators - Dermot P. Coates; Karen Hogan; Linda Kane; Rory Mulholland (National Competitiveness and Productivity Council (NCPC), 2022)
Competitiveness is a complex concept and composite indicators can be a useful tool to assess Ireland's relative strengths and weaknesses compared to international peers. Since 2020, changes in data availability and concerns with methodologies have impacted on some of the high-profile competitiveness indicators typically used by the NCPC. Global transformations such as the twin digital and green transitions and the shift towards sustainability and equality indicated the possible benefit of having the NCPC Secretariat to explore alternative indicators. In the context of global changes, it is timely to consider newly available indicators, including those on sustainability, skills, innovation and well-being, and to refresh the selection of comparator countries, in measuring Ireland's performance against key competitors and the world's best performers.
Keywords: 330